The Effect of Conflict-Cognitive Strategy in Inquiry Learning towards Pre-Service Teachers’ Critical Thinking Ability - Verawati, N. N. S. P.; Prayogi, S.; Gummah, S.; Muliadi, A.; Yusup, M. Y. (Jurnal Pendidikan IPA Indonesia, 2019)
The trend of todayÃ¢â‚¬â„¢s learning goals for educational institutions is to produce pre-service teachers who think critically. Critical thinking is a higher-order thinking domain that can be taught through appropriate learning strategies. This study intended to describe the influences of the conflict-cognitive strategy in the inquiry-based learning model towards pre-service teachersÃ¢â‚¬â„¢ critical thinking ability. This is pre-experimental research with one group pretest-posttest design. The sample included 18 pre-service physics teachers at Mataram State Islamic University (UIN Mataram). The pre-service-teachersÃ¢â‚¬â„¢ critical thinking ability was assessed using a critical thinking skill test instrument adapted from the Ennis-Weir Critical Thinking Essay Test. Indicators of critical thinking ability consisted of the ability to analyze, inference, evaluate, and make a decision. The data on critical thinking ability were analyzed descriptively and statistically, where homogeneity, normality, and t-test were performed. Descriptive analysis results indicated that the average score of critical thinking ability in the pretest was -1 in the Ã¢â‚¬Å“less criticalÃ¢â‚¬Â criteria and increased at posttest to 9,89 in the Ã¢â‚¬Å“quite criticalÃ¢â‚¬Â criteria after learning using the conflict-cognitive strategy in the inquiry-based learning model. Statistically, the analysis results revealed that the implementation of the conflict-cognitive strategy in the inquiry-based learning model had a significant effect on pre-service teachersÃ¢â‚¬â„¢ critical thinking ability. Therefore, the conflict-cognitive strategy in the inquiry-based learning model can be a reference and alternative learning strategy that can be implemented for specific purposes to improve pre-service teachersÃ¢â‚¬â„¢ critical thinking ability.